2020
DOI: 10.3390/nu12113344
|View full text |Cite
|
Sign up to set email alerts
|

Copper and Copper/Zinc Ratio in a Series of Cystic Fibrosis Patients

Abstract: Cystic fibrosis (CF) patients require a stable and sufficient supply of micronutrients. Since copper is an essential micronutrient for human development, a cross-sectional study was carried out to investigate the serum copper levels, serum copper/zinc (Cu/Zn) ratios, and their relationship with nutritional indicators in a group of CF patients. Anthropometric, biochemical, and dietary measurements, an abdominal ultrasound, and respiratory and pancreatic tests were conducted. Seventeen CF patients were studied (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 65 publications
(71 reference statements)
3
22
0
1
Order By: Relevance
“…Results showed that serum Cu and the Cu/Zn ratio had an inverse and significant correlation with age. Serum copper and zinc levels had a direct association when they were adjusted by age (Figure 2), and linear regression analysis showed that serum Cu decreased significantly with age (Figure 3), as observed in a previous study conducted in a series of CF patients [27]. Furthermore, the mean serum copper and the Cu/Zn ratios were significantly higher in children than adolescents, and the probability of finding altered Cu levels and hypercupremic cases in children (OR 3.6 and 14), children under 5 years (OR 5.8 and 7.3), and under 5 age-for-50 • Height (OR 4.4 and 6.9) was higher than in adolescents, children >5 years, and children >5 age-for-50 • Height, respectively.…”
Section: Serum Cu Levelssupporting
confidence: 82%
See 4 more Smart Citations
“…Results showed that serum Cu and the Cu/Zn ratio had an inverse and significant correlation with age. Serum copper and zinc levels had a direct association when they were adjusted by age (Figure 2), and linear regression analysis showed that serum Cu decreased significantly with age (Figure 3), as observed in a previous study conducted in a series of CF patients [27]. Furthermore, the mean serum copper and the Cu/Zn ratios were significantly higher in children than adolescents, and the probability of finding altered Cu levels and hypercupremic cases in children (OR 3.6 and 14), children under 5 years (OR 5.8 and 7.3), and under 5 age-for-50 • Height (OR 4.4 and 6.9) was higher than in adolescents, children >5 years, and children >5 age-for-50 • Height, respectively.…”
Section: Serum Cu Levelssupporting
confidence: 82%
“…Up to now, pediatric reference intervals for serum Cu have often been difficult to set up [43]. In our series of patients with chronic disease aged from 1 to 19, the mean serum Cu (118 µg/dL) was normal and there was no significant difference with the mean serum copper in a series of CF patients (113 µg/dL, p = 0.001) [27]. However, our mean serum Cu was significantly lower compared to the mean serum Cu of the German study carried out in children aged between 1 month to 18 years (20.4 ± 4.9 µmol/L or 129.6 µg/dL, p = 0.001) [44], and the study conducted in 120 healthy children (1 to 18 years of age) (134.5 µg/dL, p = 0.000) who did not receive any vitamins and mineral supplements [7] as in our series.…”
Section: Serum Cu Levelsmentioning
confidence: 65%
See 3 more Smart Citations